(untitled) (Journal of the College of Education for Women, 2019)
The Turkish relations - Israel took its course clearly about the nature and the fact thatthese relationships, and their causes and motives of its establishment, its objectives and thedimensions of the various political, security, military and economic. Orbiter and the relationsof the Turkish-Israeli It is inclusive of all the reasons for the establishment of relations, theyinclude the interpretation of an interest in international relations, which is why theestablishment of relations between the two countries and on the concept of interdependencewhere that both Turkey and Israel depends on the other in several aspects of the mostimportant military, security, economic, and to understand Turkey’s new identity, modern,where Turkey is itself a Western, it sees in response to the new identity has to be an alliancewith Israel is a tool the West in the Middle East and these data confirms the establishment ofthe giant projects which have made progress and where Turkey has become a mall to Israel.